1983
DOI: 10.1037/0735-7028.14.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and mental health: A critical reevaluation and meta-analysis.

Abstract: For many decades, lassitude and malaise have afflicted the relationship between psychology and religion. Interest and activity in this relationship are now being renewed, and old controversies wi(h new terms are resurfacing. This article reviews the extensive empirical literature on the topic and shows that religiosity is a complex phenomenon with numerous correlates and consequences that defy simple interpretations. A meta-analysis of 24 pertinent studies revealed no support for the preconception that religio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
204
0
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(223 citation statements)
references
References 61 publications
12
204
0
7
Order By: Relevance
“…On the negative side, religiosity has been associated with depression, anxiety, irrational thoughts, and low self-esteem (Judd, 1999). There are also some studies that have found no evidence of a relationship (Bergin, 1983). Recognition of the role of the adaptive and maladaptive dimensions clarifies the inconsistency in the research and also points to the idea of individual differences in how one interacts with a religion.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…On the negative side, religiosity has been associated with depression, anxiety, irrational thoughts, and low self-esteem (Judd, 1999). There are also some studies that have found no evidence of a relationship (Bergin, 1983). Recognition of the role of the adaptive and maladaptive dimensions clarifies the inconsistency in the research and also points to the idea of individual differences in how one interacts with a religion.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…In fact, whereas one would expect most measures of religiousness to have a negative association with depressive symptoms, measures of extrinsic religious motivation and negative religious coping would be expected to have a significant and positive association with depressive symptoms. The clear contrasts found here between intrinsic versus extrinsic religious motivation and positive versus negative religious coping (see Measures of religiousness in Table 3) give emphasis to the conclusions of others (e.g., Bergin, 1983;Burris, 1994;Donahue, 1985;Pargament, 1997;Richards & Bergin, 1997) and strongly suggest that researchers should attend to individuals' specific forms of religious motivation and coping.…”
Section: The Measurement Of Religiousnessmentioning
confidence: 99%
“…For example, well over 100 measures of religiousness have been published in the professional literature, with the vast majority of these assessing only positive aspects of religiousness (Hill & Hood, 1999). Scholars have long believed that some forms of religiousness are unhealthy (e.g., Bergin, 1983)-more than 100 years ago James (1902) distinguished religiousness as healthy mindedness versus the sick soul-yet research efforts on the negative forms of religiousness have been notably limited. In this meta-analysis, only 31 (21%) of the studies assessed either extrinsic religious motivations or negative religious coping.…”
Section: The Measurement Of Religiousnessmentioning
confidence: 99%
“…Rel i gi ousness i s a posi ti ve predi ctor of physi cal heal th, 12 a consi stent predi ctor of drug non-i nvol vement i n adul ts 13,53 and adol escents, 14 is related in a compl ex manner to i ssues of prejudi ce and i ntol erance 23,24,29 as w el l as mental heal th 54 and del i nquency. 23,55 It i s cl earl y an i mportant construct, deservi ng of greater attenti on from soci al sci enti sts than i t has recei ved to date.…”
Section: Intrinsic and Extrinsic Religiousness Tj Bouchard Et Al 94mentioning
confidence: 99%